2012
DOI: 10.1590/s0104-530x2012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Proposta de um método para atingir a manufatura responsiva na indústria de calçados: implantação e avaliação por meio de uma pesquisa-ação

Abstract: There are several strategies (Modern Mass Production, Lean Manufacturing, Responsive Manufacturing (RM), Mass Customization, Agile Manufacturing, etc) that can be used to aid manufacturing management in enterprises. This paper focuses on Responsive Manufacturing. RM is applied in environments of high variety of made-to-order product, in which response time (the elapsed time between the end of an inquiry and the beginning of a response) is a critical factor and should be minimum without diminishing quality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
1
0
3
Order By: Relevance
“…Outra forma de abordar o problema de leiaute é como tratada pela literatura de projeto de instalações (MUTHER, 1978;MUTHER e WHEELER, 2000;LEE et al, 1998;TEICHOLZ, 2001;BELLGRAN e SÄFSTEN, 2010;SCHENK et al, 2010;TOMPKINS et al, 2013, CHEN, 2012FERNANDES et al, 2012), com base em prévias sistematizações de conjuntos de etapas, ou passos, para o desenvolvimento do projeto do espaço, que se distinguem pelo grau de detalhamento, escopo e níveis de planejamento. Concepção que abarca e amplia a compreensão de leiaute como o desenvolvimento de um projeto conceitual, GEPROS.…”
Section: Introductionunclassified
“…Outra forma de abordar o problema de leiaute é como tratada pela literatura de projeto de instalações (MUTHER, 1978;MUTHER e WHEELER, 2000;LEE et al, 1998;TEICHOLZ, 2001;BELLGRAN e SÄFSTEN, 2010;SCHENK et al, 2010;TOMPKINS et al, 2013, CHEN, 2012FERNANDES et al, 2012), com base em prévias sistematizações de conjuntos de etapas, ou passos, para o desenvolvimento do projeto do espaço, que se distinguem pelo grau de detalhamento, escopo e níveis de planejamento. Concepção que abarca e amplia a compreensão de leiaute como o desenvolvimento de um projeto conceitual, GEPROS.…”
Section: Introductionunclassified
“…Currently available QRM literature mostly covers the description and development of QRM's principles, e.g., Suri (2014) and Suri (1998Suri ( , 2010a, and case studies on its implementation, e.g., Fernandes et al (2012), Veloso Saes and Godinho Filho (2011), and the POLCA (Paired-cell Overlapping Loops of Cards with Authorization) system implementation, e.g., Chinet and Godinho Filho (2014), Fernandes and do Carmo-Silva (2006), Germs and Riezebos (2010), Krishnamurthy and Suri (2009), Suri (1998), and Vandaele et al (2008). Godinho Filho and Veloso Saes (2013), through a review of literature on reducing lead time within the context of Time-Based Competition and QRM, concluded that much of the literature on the subject is quite limited with regard to practical studies, with some little exception (for example Vandaele et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…O QRM é uma abordagem pouco explorada no Brasil, estudado principalmente nos Estados Unidos, local onde se originou. Consideram-se aqui pesquisas realizadas em âmbito nacional, podendo--se destacar como contribuições alguns dos trabalhos realizados por Godinho Filho, tais como: Godinho Filho et al (2011);Fernandes et al (2012); Godinho Filho; Veloso Saes (2013); Lima et al (2013) e Soulé et al (2016. A pesquisa está estruturada da seguinte forma: a seção inicial apresenta o tema investigado; a segunda seção elenca os principais conceitos referentes ao QRM, a fim de situar sobre o tema de pesquisa.…”
unclassified